Looking after your partner: sentinel behaviour in a socially monogamous bird - Mainwaring,Mark C.; Griffith,Simon C. (PeerJ, 2013)
Natural selection favours those individuals with effective anti-predator defences. The presence of sentinels is known to be an effective form of defence amongst stable groups of individuals within cooperative and polygynous breeding systems. However, the presence of sentinels in the more prevalent socially monogamous breeding systems remains overlooked as an important benefit of such partnerships. Here, we describe a study in which we examined the presence and effectiveness of sentinels in a wild population of the socially monogamous zebra finch (Taeniopygia guttata). We found that when experimentally approached by a human observer during incubation, birds flushed from their nests at significantly greater distances when their reproductive partner was acting as a sentinel than when the partner was absent. The distance at which birds flushed was not influenced by the approach direction of the human observer, the gender of the incubating bird, the presence of conspecifics, the habitat type or the size of the breeding colony. Our results indicate that sentinels are an effective anti-predator defence amongst socially monogamous birds, and may represent a neglected benefit of the formation of stable social partnerships in birds. We suggest that whilst recent work has focused on the sexual conflicts that occur between males and females in socially monogamous pairs, we should not lose sight of the benefits that individuals may gain from their partner.
Keywords: Incubation; Zebra finch; Predation; Bi-parental care; Natural selection; Sentinels; Social monogamy; Taeniopygia guttata